2019
DOI: 10.1002/lio2.262
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes for dental health, shoulder‐neck dysfunction, and overall quality of life after treatment with radiation for head and neck cancer

Abstract: Objectives The current exploratory cross‐sectional study was designed to examine and characterize survivorship issues among patients treated with radiation for head and neck cancer with regard to dental health, shoulder‐neck dysfunction, and overall quality of life (QOL). Methods Patients (N = 58) being seen for follow‐up at a radiation oncology clinic at least 1 year beyond the end of treatment completed three survey questionnaires regarding general QOL as well as dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Possible mechanisms include transient trauma to the spinal accessory nerve with variable recovery, radiation‐induced fibrotic changes to the neck and shoulder, or disuse with subsequent decline in function 15,16 . Regardless of aetiology, shoulder pain and dysfunction after oncologic treatment may greatly affect QOL and functional status, including ability to perform daily activity, sleep comfortably, and lift objects 17 . This QOL impact has been well‐studied after ND with estimates that even 25%–50% of patients will demonstrate some degree of shoulder deficits postoperatively, even with selective NDs 18–20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible mechanisms include transient trauma to the spinal accessory nerve with variable recovery, radiation‐induced fibrotic changes to the neck and shoulder, or disuse with subsequent decline in function 15,16 . Regardless of aetiology, shoulder pain and dysfunction after oncologic treatment may greatly affect QOL and functional status, including ability to perform daily activity, sleep comfortably, and lift objects 17 . This QOL impact has been well‐studied after ND with estimates that even 25%–50% of patients will demonstrate some degree of shoulder deficits postoperatively, even with selective NDs 18–20 .…”
Section: Discussionmentioning
confidence: 99%
“…Identifying the prevalence of neck and shoulder dysfunction and the good prognosis for recovery after HPV + OPSCC treatment is important in improving patient counselling about treatment choices and recovery trajectory. For instance, Verma et al previously found that in a population of patients treated for head and neck SCC, nearly 40% experienced nocturnal neck or shoulder pain but only 31% reported being counselled regarding potential shoulder problems prior to treatment 17 . Additionally, our study observation that patients primarily experienced decline in social and functional activities such as recreation, lifting objects, and performing daily work is especially notable given that persistent reductions in physical activity have been correlated with fatigue and reduced social and emotional well‐being in head and neck cancer survivors 26 .…”
Section: Discussionmentioning
confidence: 99%
“…For advanced unresectable HNSCC, definitive chemoradiotherapy, definitive radiotherapy, palliative chemotherapy or palliative radiotherapy are employed based on multiple parameters like age, performance status, etc 3. In this subgroup of patients, the correct approach to treatment is often decided considering the best impact on quality of life (QoL) and on survivorship issues 3.…”
Section: Introductionmentioning
confidence: 99%
“…For advanced unresectable HNSCC, definitive chemoradiotherapy, definitive radiotherapy, palliative chemotherapy or palliative radiotherapy are employed based on multiple parameters like age, performance status, etc 3. In this subgroup of patients, the correct approach to treatment is often decided considering the best impact on quality of life (QoL) and on survivorship issues 3. For instance, and combined chemoradiotherapy may confer a worse QoL than radiotherapy alone, and intensity modulated radiotherapy may yield a better QoL than conventional radiotherapy.…”
Section: Introductionmentioning
confidence: 99%